Packaging material and preparation method and application thereof
By selecting an epoxy resin matrix that matches the thermal expansion coefficient of the silicon cells and adding fluorinated polymer fillers and nano-silicon particles, the problem of micro-cracks caused by thermal stress during the high-temperature curing process of the packaging material is solved, significantly improving the performance of the solar cell module. performance and reliability.
Patent Information
- Application Number
- CN202411432235.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-21
AI Technical Summary
During the high-temperature curing process, existing packaging materials have thermal stress caused by mismatch in the thermal expansion coefficient and material rigidity, forming microcracks, affecting the performance and life of solar cell modules.
Use an epoxy resin matrix that matches the thermal expansion coefficient of the silicon cell, such as high-performance two-component epoxy resin or nitrogen-containing epoxy silicone resin, and add fluorinated polymer fillers and nano-silica particles, and modify it to reduce heat stress.
It effectively reduces micro-cracks caused by thermal stress, improves the overall performance and reliability of solar cell modules, and enhances the flexibility and thermal adaptability of the material.
Smart Images

Figure BDA0005083963860000111 
Figure BDA0005083963860000121
Abstract
Description
Technical Field
[0001] The invention relates to a packaging material and a preparation method and application thereof, belonging to the technical field of batteries. Background Art
[0002] In the production of solar cell modules, the encapsulation process is one of the key links. The selection of encapsulation materials has a significant impact on the performance and life of the module. Currently, the widely used encapsulation materials mainly include EVA (ethylene-vinyl acetate copolymer) and polyurethane. These materials will cause thermal stress during the high-temperature curing process due to the difference in thermal expansion coefficient and the rigidity of the material itself, thereby generating microcracks on the surface or inside of the cell.
[0003] The deficiencies of the prior art mainly include the following aspects: (1) Mismatch in thermal expansion coefficient: The thermal expansion coefficient of existing packaging materials, such as traditional EVA films, is significantly different from that of battery cell materials (such as silicon). During the production process, the mismatch in thermal expansion coefficients between the packaging material and the battery cell will lead to thermal stress concentration and the formation of microcracks. Such microcracks will reduce the photovoltaic conversion efficiency of the battery cell and may expand during long-term use, further damaging component performance. (2) Rigidity of packaging materials: Traditional packaging materials such as polyurethane have high rigidity and lack sufficient elasticity to cope with the stress caused by temperature changes. This rigidity limits the material's ability to deform, making it difficult to effectively disperse and relieve thermal stress, thereby increasing the risk of microcracks. Summary of the invention
[0004] In view of this, the present invention provides a packaging material and a preparation method and application thereof. The technical problem to be solved is to reduce the thermal stress of the material during the heat treatment process by selecting an epoxy resin matrix that matches the thermal expansion coefficient of the silicon cell, such as a high-performance two-component epoxy resin or a nitrogen-containing epoxy silicone resin, and performing a modification treatment, thereby effectively reducing the microcracks caused by thermal stress.
[0005] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions: The present invention provides a packaging material, which includes epoxy resin, and the epoxy resin is added with fluorinated polymer filler and nano silicon particles.
[0006] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0007] Preferably, in the aforementioned packaging material, the epoxy resin comprises an epoxy resin matrix and a curing agent in a mass ratio of 2:1-4:1.
[0008] Preferably, in the aforementioned packaging material, the thermal expansion coefficient of the epoxy resin is 6×10- 6 / K.
[0009] Preferably, in the aforementioned packaging material, the epoxy resin matrix is epoxy resin 2000, solid bisphenol A epoxy resin, bisphenol F epoxy resin, liquid bisphenol A epoxy resin, glycidylamine epoxy silicone resin or polyisocyanurate-oxazolidone resin.
[0010] Preferably, in the aforementioned packaging material, the added amount of the fluorinated polymer filler is 5%-10% (v / v).
[0011] Preferably, in the aforementioned packaging material, the fluorinated polymer filler is polytetrafluoroethylene, polyvinylidene fluoride, fluororubber, fluorinated ethylene propylene rubber, perfluoroether rubber or fluorosilicone rubber.
[0012] Preferably, in the aforementioned packaging material, the added amount of the nano silicon particles is 0.5wt%-2wt%.
[0013] Preferably, in the aforementioned packaging material, the diameter of the nano silicon particles is 10-50 nanometers.
[0014] The purpose of the present invention and the technical problem solved by the present invention can also be achieved by the following technical measures: A method for preparing a packaging material proposed by the present invention comprises the following steps: uniformly mixing epoxy resin and curing agent, and then sequentially adding fluorinated polymer filler and nano silicon particles thereto to obtain the packaging material.
[0015] The purpose of the present invention and the solution to its technical problems can also be achieved by adopting the following technical measures. A method for reducing microcracks in the production process of solar cell modules proposed by the present invention comprises the following steps:
[0016] The packaging material is coated on the surface of the solar cell chip, and the packaging material is cured at 80-120° C. for 2-4 hours to complete the packaging; the packaged solar cell chip is assembled with a back plate and a glass cover to obtain the solar cell module.
[0017] Compared with the prior art, the packaging material and the preparation method and application thereof of the present invention have the following beneficial effects:
[0018] The present invention reduces the thermal stress of the material during heat treatment by selecting an epoxy resin matrix that matches the thermal expansion coefficient of the silicon cell, such as a high-performance two-component epoxy resin or a nitrogen-containing epoxy silicone resin, and performing a modification treatment, thereby effectively reducing the microcracks of the cell caused by thermal stress. After adding fluorinated polymer fillers and nano-silicon particles, the flexibility and thermal adaptability of the epoxy resin material are significantly improved, and it can better cope with the stress caused by temperature changes, further reducing the risk of microcracks and improving the overall performance and reliability of the component.
[0019] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0020] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a packaging material and its preparation method and its specific implementation, structure, characteristics and effects of the application according to the present invention in combination with the preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0021] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.
[0022] Some embodiments of the present invention provide a packaging material, which includes epoxy resin, to which fluorinated polymer filler and nano silicon particles are added. This configuration is to optimize the packaging material to solve micro cracks in the production process of solar cell modules.
[0023] In the above technical solution, the fluorinated polymer filler enhances the thermal stability and flexibility of the material and reduces the influence of thermal stress on the material; the nano-silicon particles enhance the thermal conductivity of the material, improve the mechanical properties of the material and reduce the stress caused by thermal expansion.
[0024] In some optional embodiments, the epoxy resin comprises an epoxy resin matrix and a curing agent. The epoxy resin matrix provides good adhesion and stability. The mass ratio of the epoxy resin matrix to the curing agent is generally between 2:1 and 4:1, preferably 2:1.
[0025] Among all factors, the type of epoxy resin matrix is usually the most critical because it directly determines the basic properties of the packaging material, including mechanical strength, weather resistance and chemical stability. The epoxy resin matrix is the main component of the entire material, and its selection will have a fundamental impact on the effects of other additives. Therefore, in some optional embodiments, the epoxy resin matrix can be selected from high-performance two-component epoxy resins such as epoxy resin 2000 (EPOXY-2000), solid bisphenol A epoxy resin, bisphenol F epoxy resin, liquid bisphenol A epoxy resin, or nitrogen-containing epoxy silicone resins such as glycidylamine epoxy silicone resin, polyisocyanurate-oxazolidone resin, etc.
[0026] Epoxy resin matrix, such as high-performance two-component epoxy resin (such as EPOXY2000), generally has a high coefficient of thermal expansion (CTE) and is usually difficult to be compatible with silicon cells (2.6-3.6×10- 6 / K). However, by adding fillers or modifiers, the thermal expansion coefficient of epoxy resin can be effectively reduced, making it closer to the thermal expansion coefficient CTE of silicon cells. Accordingly, in some optional embodiments, the thermal expansion coefficient of the epoxy resin can reach 6×10- 6 / K. This allows the thermal expansion coefficient of the packaging material to match the silicon cell.
[0027] Curing agent plays a decisive role in the curing process of encapsulation materials, affecting the final curing effect and the physical and chemical properties of the material: Curing speed and temperature sensitivity: Different curing agents require different curing conditions, such as temperature and time. This will affect the operability and processing efficiency of the encapsulation material in the production process. Cross-linking density: The type and amount of curing agent determine the cross-linking density of the epoxy resin molecular chain, which in turn affects the hardness, elasticity and heat resistance of the material. Higher cross-linking density usually means higher strength and heat resistance, but toughness may decrease. Resistance to chemical corrosion and hydrolysis: Certain curing agents give materials stronger resistance to chemical corrosion and water resistance, which is very important for the durability of photovoltaic panels in long-term outdoor use. The choice of curing agent directly affects the mechanical properties, heat resistance and chemical resistance of the material, and is the key to ensuring that the epoxy resin matrix fully realizes its potential. The type of curing agent affects the cross-linking density and final performance of the material, and the interaction with the matrix is also crucial. In some optional embodiments, the curing agent selects a chemical that is insensitive to temperature changes, such as an amine curing agent (for example: Dicyandiamide). The amine-based curing agent can be selected from the following types: 1. Aromatic amine curing agent: It usually has a high curing speed and hardening effect, and is suitable for applications that require fast curing. Typical examples include dimethylbenzene (DDM) and diethylenediamine (DEA). 2. Aliphatic amine curing agent: It usually has good heat resistance and chemical resistance, and is suitable for applications in high temperature environments. For example, ethylenediamine (EDA) and triethylenetetramine (TEPA). 3. Alicyclic amine curing agent: It has a cyclic structure and usually provides good weather resistance and hydrolysis resistance. After the epoxy resin is cured, these cyclic curing agents help to enhance the durability of the material. Typical examples include cyclohexylamine. 4. Fatty amine curing agent: Its structure is between aliphatic amines and aromatic amines, and it usually has good comprehensive properties. For example, isocyanate-modified amines. 5. Mixed amine curing agent: Some curing agents are multifunctional mixtures that combine the characteristics of different types of curing agents to achieve more comprehensive performance requirements.
[0028] The type and amount of fluorinated polymer fillers have a significant impact on the weather resistance, water resistance and mechanical properties of the material. Fluorinated polymer fillers are often used to improve the weather resistance and UV resistance of packaging materials, and can also reduce the water absorption rate of the material. Its specific impacts include: Weather resistance: Fluorinated polymers generally have excellent UV resistance, which can significantly increase the life of the material in outdoor use and reduce aging and discoloration caused by sunlight; Water resistance: Fluorinated polymers have a very low water absorption rate, which can improve the moisture resistance of packaging materials and prevent water vapor from invading the interior of the material and affecting the long-term performance of photovoltaic panels; Chemical resistance: Certain fluorinated polymers can improve the material's resistance to acid and alkali corrosion, ensuring that photovoltaic packaging materials remain stable under extreme climatic conditions; To this end, in some optional embodiments, the amount of fluorinated polymer fillers added can be set to 5%-10% (v / v). Adding fluorinated polymer fillers in this range can improve the weather resistance, chemical corrosion resistance and mechanical strength of packaging materials. However, if the addition amount is greater than 10% (v / v), too much filler may cause the toughness of the material to decrease, or even increase the brittleness of the material; if the addition amount is less than 5% (v / v), the weather resistance, chemical corrosion resistance and mechanical strength of the encapsulation material may be reduced. The amount of filler added will also affect the processing properties of the encapsulation material, such as fluidity and curing time. If the addition amount is greater than 10% (v / v), excessive addition will make the encapsulation material difficult to form and affect the production process; and if the addition amount is less than 5% (v / v), the processing performance may be reduced.
[0029] In addition, the change in the type of fluorinated polymer fillers mainly affects the weather resistance and aging resistance of the material, which is particularly critical for the performance of photovoltaic panels exposed to the external environment for a long time. Fluorinated polymer fillers generally include the following types, which can be selected according to the application scenario: 1. Polytetrafluoroethylene (PTFE) is one of the most common fluorinated polymers, with excellent chemical inertness, high temperature resistance and extremely low friction coefficient. It is often used to enhance the wear resistance and chemical stability of composite materials. As a filler, PTFE can be used in lubricating materials, sealing materials, and corrosion-resistant coatings. 2. Polyvinylidene fluoride (PVDF) has good chemical stability and weather resistance, especially in acidic and alkaline environments. It is often used as a filler in electrical insulation and corrosion-resistant coatings, which can significantly improve the durability and aging resistance of the material. PVDF also has good mechanical strength and heat resistance. 3. Fluororubber (FKM) is mainly used in applications requiring high temperature and high chemical stability, such as seals and gaskets. As a filler, it can enhance the heat resistance and chemical resistance of composite materials and is widely used in the automotive, aerospace and petrochemical fields. 4. Fluorinated ethylene propylene rubber (FEPM) is a fluorinated polymer similar to FKM, but its chemical stability and heat resistance are different. It is mainly used for cable outer sheaths and high-temperature resistant sealing materials, which can improve the chemical corrosion resistance and high-temperature stability of composite materials. 5. Perfluoroether rubber (FFKM) is a high-performance material of fluorinated rubber with very good chemical corrosion resistance and high-temperature resistance. It is often used as a sealing filler under high temperature and high pressure, and is widely used in industries such as semiconductor manufacturing and chemical processing that require extremely high chemical resistance and temperature stability. 6. Fluorosilicone rubber (FVMQ) is a silicone rubber containing fluorine elements, which has the advantages of both fluoropolymers and silicone rubbers, and has excellent chemical resistance and low-temperature performance. As a filler, FVMQ is mainly used in the aerospace and automotive industries to improve the durability and stability of the material in extreme environments. Different types of fluorinated polymer fillers each have unique properties, and suitable materials can be selected according to specific application requirements to enhance the performance of composite materials.
[0030] Nano silicon particles are used as auxiliary reinforcing materials, and their addition amount affects the strengthening effect of the material. In some optional embodiments, the addition amount of the nano silicon particles can be set to 0.5wt%-2wt%. Nano particles in this addition amount range can improve the mechanical properties and thermal stability of the packaging material; if the addition amount is less than 0.5wt%, the mechanical properties and thermal stability of the packaging material will be reduced; but if the addition amount exceeds 2wt%, too much addition may cause agglomeration effect and reduce performance.
[0031] In some optional embodiments, the diameter of the nano silicon particles is 10-50 nanometers. The size setting needs to consider the following factors and their effects: 1. Light absorption efficiency: The particle size of 10-50 nanometers can effectively improve the light absorption efficiency. Nano-scale particles can produce quantum confinement effects and enhance light absorption. When it is less than 10 nanometers, the particle size is too small, which may lead to insufficient light scattering ability, thereby reducing the absorption efficiency of light of a specific wavelength and affecting the photoelectric conversion effect. When it exceeds 50 nanometers, the particle size is too large, the quantum confinement effect is weakened, the light absorption ability decreases, and the light transmittance of the material may be negatively affected. 2. Charge carrier transport performance: Nano-scale silicon particles help optimize the transmission of electrons and holes, reduce the recombination rate, and improve the efficiency of photovoltaic devices. Particle sizes below 10 nanometers may cause the carrier transmission path to become shorter, the recombination probability to increase, and affect the overall conductivity. Particle sizes exceeding 50 nanometers may increase the electron transmission path, thereby increasing the scattering and recombination opportunities of carriers and reducing the charge separation efficiency. 3. Material uniformity and packaging stability: The particle size of 10-50 nanometers can ensure the uniform distribution of the material in the packaging layer and maintain the stability of the structure. Particles below 10 nanometers may be difficult to distribute evenly and are prone to agglomeration, affecting the integrity and stability of the packaging layer. Particles exceeding 50 nanometers are unevenly distributed in the packaging material, which may lead to a decrease in the mechanical strength of the packaging layer and affect long-term stability. 4. Mechanical strength and thermal stability: Appropriate particle size helps to improve the mechanical strength and thermal stability of the packaging material, so that the photovoltaic panel can withstand thermal and mechanical stresses during long-term use. When the particle size is below 10 nanometers, the particle may not have enough surface area and cannot effectively enhance the mechanical properties of the packaging layer. When the particle size exceeds 50 nanometers, the particle may form a large defect area, reduce the mechanical strength and heat resistance of the material, and affect the service life of the photovoltaic panel. Therefore, the diameter of the nano-silicon particles is set to 10-50 nanometers in order to achieve the optimal balance in terms of light absorption, charge transfer, material uniformity and mechanical properties. Too small or too large a particle size will affect the overall performance of the photovoltaic packaging material.
[0032] Some embodiments of the present invention also provide a method for preparing a packaging material, comprising the following steps: uniformly mixing the epoxy resin and the curing agent according to the above-mentioned proportions, and then sequentially adding a fluorinated polymer filler and nano-silicon particles thereto to obtain the packaging material.
[0033] In specific implementation, the preparation method comprises the following steps:
[0034] S1 Mix epoxy resin and curing agent: According to the above proportions, mix epoxy resin EPOXY-2000 and amine-based curing agent in a clean container;
[0035] S2 Adding polytetrafluoroethylene and nano silicon particles: According to the above ratio, polytetrafluoroethylene is gradually added to the mixture of epoxy resin and curing agent; then nano silicon particles with a diameter of 30 nanometers are added;
[0036] S3 stirring and mixing: using a stirring rod to stir and mix thoroughly to ensure that the polytetrafluoroethylene and nano-silicon particles are evenly dispersed in the epoxy resin until a uniform mixture is obtained;
[0037] S4 pours the obtained mixture into the encapsulation mold, ensuring that the mold is fully filled and the surface is leveled.
[0038] Some embodiments of the present invention also provide a method for reducing microcracks in a solar cell module production process, comprising the following steps:
[0039] 1) Apply the above encapsulation material on the surface of the solar cell chip to ensure uniform coverage and no bubbles.
[0040] 2) According to the curing requirements of the packaging material, the packaging material is cured at 80-120°C for 2-4 hours to complete the packaging to ensure that it has the required performance and stability.
[0041] 3) Assemble the packaged solar cell chips with other components (such as backplane, glass cover, etc.) to obtain a complete solar cell module. Ensure that the edges and joints of the solar cell module are well sealed to prevent moisture and dust from entering and affecting the performance of the cell. Test the produced solar cell modules to check whether their electrical performance and appearance quality meet the requirements. Perform quality control to ensure that the produced solar cell modules meet the expected performance indicators. Package the solar cell modules that pass the test to ensure that they are not damaged during transportation and storage. Store the solar cell modules in a dry, light-proof and temperature-appropriate environment to maintain their performance and life.
[0042] Through the above technical scheme, the epoxy resin packaging material containing polytetrafluoroethylene and nano silicon particles can be successfully applied to the production process of solar cell modules. The packaging material of the present invention can reduce the generation of micro cracks in solar cell sheets and improve the durability, stability and other performance of solar cell modules.
[0043] The present invention is further described below in conjunction with specific embodiments.
[0044] Example 1
[0045] This embodiment provides a packaging material, which includes epoxy resin, to which 8% (v / v) polytetrafluoroethylene and 1wt% nano-silicon particles (with a diameter of 30 nanometers) are added; the epoxy resin includes EPOXY-2000 and an amine-based curing agent in a mass ratio of 2:1.
[0046] The method for preparing the packaging material comprises the following steps:
[0047] a. According to the above ratio, epoxy resin EPOXY-2000 and amine curing agent are mixed evenly in a clean container to obtain a first mixture;
[0048] b. adding 8% (v / v) polytetrafluoroethylene to the first mixture obtained in step a, and then adding 1wt% nano-silicon particles (with a diameter of 30 nanometers) thereto, and stirring and mixing them thoroughly with a stirring rod until a uniform second mixture is obtained;
[0049] c. Pour the second mixture obtained in step b into the packaging mold, so that the second mixture fully fills the mold and smoothes the surface, thereby obtaining the packaging material.
[0050] Example 2
[0051] The difference between this embodiment and embodiment 1 is that the mass ratio of the epoxy resin matrix to the curing agent in this embodiment is 3:1, and the other parameters and steps are the same as those in embodiment 1.
[0052] Example 3
[0053] The difference between this embodiment and embodiment 1 is that the mass ratio of the epoxy resin matrix to the curing agent in this embodiment is 4:1, and the other parameters and steps are the same as those in embodiment 1.
[0054] Example 4
[0055] The difference between this embodiment and embodiment 1 is that the addition amount of polytetrafluoroethylene in this embodiment is 5% (v / v), and the other parameters and steps are the same as those in embodiment 1.
[0056] Example 5
[0057] The difference between this embodiment and embodiment 1 is that the addition amount of polytetrafluoroethylene in this embodiment is 10% (v / v), and the other parameters and steps are the same as those in embodiment 1.
[0058] Example 6
[0059] The difference between this embodiment and embodiment 1 is that the fluorinated polymer filler in this embodiment is polyvinylidene fluoride, and the other parameters and steps are the same as those in embodiment 1.
[0060] Example 7
[0061] The difference between this embodiment and embodiment 1 is that the fluorinated polymer filler in this embodiment is fluororubber, and the other parameters and steps are the same as those in embodiment 1.
[0062] Example 8
[0063] The difference between this embodiment and embodiment 1 is that the fluorinated polymer filler in this embodiment is fluorinated ethylene propylene rubber, and the other parameters and steps are the same as those in embodiment 1.
[0064] Example 9
[0065] The difference between this embodiment and embodiment 1 is that the fluorinated polymer filler in this embodiment is perfluoroether rubber, and the other parameters and steps are the same as those in embodiment 1.
[0066] Example 10
[0067] The difference between this embodiment and embodiment 1 is that the fluorinated polymer filler in this embodiment is fluorosilicone rubber, and the other parameters and steps are the same as those in embodiment 1.
[0068] Embodiment 11
[0069] The difference between this embodiment and embodiment 1 is that the addition amount of the nano silicon particles in this embodiment is 0.5 wt %, and the other parameters and steps are the same as those in embodiment 1.
[0070] Example 12
[0071] The difference between this embodiment and embodiment 1 is that the addition amount of the nano silicon particles in this embodiment is 2 wt %, and the other parameters and steps are the same as those in embodiment 1.
[0072] Embodiment 13
[0073] The difference between this embodiment and embodiment 1 is that the diameter of the nano silicon particles in this embodiment is 10 nanometers, and the other parameters and steps are the same as those in embodiment 1.
[0074] Embodiment 14
[0075] The difference between this embodiment and embodiment 1 is that the diameter of the nano silicon particles in this embodiment is 50 nanometers, and the other parameters and steps are the same as those in embodiment 1.
[0076] Comparative Example 1
[0077] The difference between this comparative example and Example 1 is that the mass ratio of the epoxy resin matrix to the curing agent in this comparative example is 1:1, and the other parameters and steps are the same as those in Example 1.
[0078] Comparative Example 2
[0079] The difference between this comparative example and Example 1 is that the mass ratio of the epoxy resin matrix to the curing agent in this comparative example is 5:1, and the other parameters and steps are the same as those in Example 1.
[0080] Comparative Example 3
[0081] The difference between this comparative example and Example 1 is that the amount of polytetrafluoroethylene added in this comparative example is 3% (v / v), and the other parameters and steps are the same as those in Example 1.
[0082] Comparative Example 4
[0083] The difference between this comparative example and Example 1 is that the amount of polytetrafluoroethylene added in this comparative example is 12% (v / v), and the other parameters and steps are the same as those in Example 1.
[0084] Comparative Example 5
[0085] The difference between this comparative example and Example 1 is that the addition amount of the nano silicon particles in this comparative example is 0.3 wt %, and the other parameters and steps are the same as those in Example 1.
[0086] Comparative Example 6
[0087] The difference between this comparative example and Example 1 is that the addition amount of the nano silicon particles in this comparative example is 2.5 wt %, and the other parameters and steps are the same as those in Example 1.
[0088] Comparative Example 7
[0089] The difference between this comparative example and Example 1 is that the diameter of the nano silicon particles in this comparative example is 8 nanometers, and the other parameters and steps are the same as those in Example 1.
[0090] Comparative Example 8
[0091] The difference between this comparative example and Example 1 is that the diameter of the nano silicon particles in this comparative example is 55 nanometers, and the other parameters and steps are the same as those in Example 1.
[0092] Comparative Example 9
[0093] The difference between this comparative example and Example 1 is that this comparative example does not contain fluorinated polymer filler, and the other parameters and steps are the same as Example 1.
[0094] Comparative Example 10
[0095] The difference between this comparative example and Example 1 is that this comparative example does not contain nano silicon particles, and the other parameters and steps are the same as Example 1.
[0096] Comparative Example 11
[0097] The difference between this comparative example and Example 1 is that this comparative example does not contain fluorinated polymer filler and nano silicon particles, and the other parameters and steps are the same as Example 1.
[0098] Comparative Example 12
[0099] The difference between this comparative example and Example 1 is that this comparative example does not contain a curing agent, and the other parameters and steps are the same as Example 1.
[0100] Comparative Example 13
[0101] The difference between this comparative example and Example 1 is that this comparative example does not contain a curing agent, a fluorinated polymer filler and nano-silicon particles, and the remaining parameters and steps are the same as Example 1.
[0102] The packaging materials obtained in Examples 1-14 and Comparative Examples 1-13 were subjected to contact angle test, FTIR analysis test and thermogravimetric analysis test. The test results are shown in Table 1.
[0103] Table 1
[0104]
[0105]
[0106] It can be seen from the data in Table 1 that the water contact angle of the packaging materials described in Examples 1-14 of the present invention is between 68° and 77°, the characteristic peak positions of the FTIR analysis are between 1235 cm^-1 and 1245 cm^-1 and 2920 cm^-1 and 2935 cm^-1, and the weight loss temperature of the thermogravimetric analysis is between 315°C and 327°C.
[0107] Compared with Example 1, as the mass ratio of the epoxy resin matrix and the curing agent increases, the water contact angles of Examples 2 and 3 decrease, the positions of the characteristic peaks move, and the weight loss temperatures decrease.
[0108] Compared with Example 1, as the amount of polytetrafluoroethylene added decreases, the water contact angle of Example 4 increases, the position of the characteristic peak moves, and the weight loss temperature increases.
[0109] Compared with Example 1, as the amount of polytetrafluoroethylene added increases, the water contact angle of Example 5 increases, the position of the characteristic peak moves, and the weight loss temperature increases.
[0110] Compared with Example 1, since polytetrafluoroethylene is changed to polyvinylidene fluoride, the water contact angle of Example 6 is reduced, the position of the characteristic peak is moved, and the weight loss temperature is also reduced.
[0111] Compared with Example 1, since polytetrafluoroethylene is changed to fluororubber, the water contact angle of Example 7 increases, the position of the characteristic peak moves, and the weight loss temperature increases.
[0112] Compared with Example 1, since polytetrafluoroethylene is changed to fluorinated ethylene-propylene rubber, the water contact angle of Example 8 increases, the position of the characteristic peak moves, and the weight loss temperature increases.
[0113] Compared with Example 1, since polytetrafluoroethylene is changed to perfluoroether rubber, the water contact angle of Example 9 is reduced, the position of the characteristic peak is moved, and the weight loss temperature is also reduced.
[0114] Compared with Example 1, since polytetrafluoroethylene is changed to fluorosilicone rubber, the water contact angle of Example 10 is significantly increased, the position of the characteristic peak is shifted, and the weight loss temperature is also increased.
[0115] Compared with Example 1, as the amount of nano-silicon particles added decreases, the water contact angle of Example 11 decreases, the position of the characteristic peak moves, and the weight loss temperature decreases.
[0116] Compared with Example 1, as the amount of nano-silicon particles added increased, the water contact angle of Example 12 did not change, the position of the characteristic peak moved, and the weight loss temperature did not change.
[0117] Compared with Example 1, as the diameter of the nano-silicon particles decreases, the water contact angle of Example 13 decreases, the position of the characteristic peak moves, and the weight loss temperature decreases.
[0118] Compared with Example 1, as the diameter of the nano-silicon particles increases, the water contact angle of Example 14 decreases, the position of the characteristic peak moves, and the weight loss temperature decreases.
[0119] Compared with Example 1, as the mass ratio of the epoxy resin matrix and the curing agent decreases, the water contact angle of Comparative Example 1 decreases significantly, the position of the characteristic peak moves significantly, and the weight loss temperature decreases.
[0120] Compared with Example 1, as the mass ratio of the epoxy resin matrix and the curing agent increases, the water contact angle of Comparative Example 2 decreases significantly, the position of the characteristic peak moves significantly, and the weight loss temperature decreases.
[0121] Compared with Example 1, as the amount of polytetrafluoroethylene added decreases, the water contact angle of Comparative Example 3 decreases significantly, the position of the characteristic peak moves significantly, and the weight loss temperature decreases.
[0122] Compared with Example 1, as the amount of polytetrafluoroethylene added is significant, the water contact angle of Comparative Example 4 is significantly reduced, the position of the characteristic peak is significantly moved, and the weight loss temperature is reduced.
[0123] Compared with Example 1, as the amount of nano-silicon particles added decreases, the water contact angle of Comparative Example 5 decreases significantly, the position of the characteristic peak moves significantly, and the weight loss temperature decreases.
[0124] Compared with Example 1, as the amount of nano-silicon particles added increases, the water contact angle of Comparative Example 6 decreases significantly, the position of the characteristic peak moves significantly, and the weight loss temperature decreases.
[0125] Compared with Example 1, as the diameter of the nano-silicon particles decreases, the water contact angle of Comparative Example 7 decreases significantly, the position of the characteristic peak moves significantly, and the weight loss temperature decreases.
[0126] Compared with Example 1, as the diameter of the nano-silicon particles increases, the water contact angle of Comparative Example 8 decreases significantly, the position of the characteristic peak moves significantly, and the weight loss temperature decreases.
[0127] Compared with Example 1, Comparative Example 9 does not contain a fluorinated polymer filler, and its water contact angle is significantly reduced, the position of the characteristic peak is significantly moved, and the weight loss temperature is reduced.
[0128] Compared with Example 1, Comparative Example 10 does not contain nano-silicon particles, its water contact angle is significantly reduced, the position of the characteristic peak is significantly moved, and the weight loss temperature is reduced.
[0129] Compared with Example 1, Comparative Example 11 does not contain fluorinated polymer fillers and nano-silicon particles, and its water contact angle is significantly reduced, the position of the characteristic peak is significantly moved, and the weight loss temperature is reduced.
[0130] Compared with Example 1, Comparative Example 12 does not contain a curing agent, its water contact angle is significantly reduced, the position of the characteristic peak is significantly moved, and the weight loss temperature is reduced.
[0131] Compared with Example 1, Comparative Example 13 does not contain a curing agent, a fluorinated polymer filler, and nano-silicon particles, and its water contact angle is significantly reduced, the position of the characteristic peak is significantly moved, and the weight loss temperature is reduced.
[0132] Thermogravimetric analysis can evaluate the stability of modified materials at high temperatures. From the above data, it can be seen that by selecting an epoxy resin matrix that matches the thermal expansion coefficient of the silicon cell, such as a high-performance two-component epoxy resin or a nitrogen-containing epoxy silicone resin, and performing a modification treatment, the thermal stress of the material during the heat treatment process is reduced, thereby effectively reducing the microcracks caused by thermal stress, thereby selecting materials suitable for the packaging process to reduce the problem of hidden cracks caused by high temperatures during the packaging process of solar cells. The optimization of modified materials can improve the heat resistance of solar cells, thereby better protecting the surface of solar cells during the packaging process and reducing the occurrence of hidden cracks. The optimized modified material has a significant improvement in superhydrophobic performance, and also improves in thermal stability, which can provide better sealing effects and protection performance, and reduce damage to solar cells during the packaging process.
[0133] The above embodiments are only used to explain the content of the present invention, and are not intended to limit the present invention. Simple technical variations within the technical concept of the present invention should be considered to be covered by the content disclosed by the present invention and belong to the protection scope of the present invention.
[0134] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.
[0135] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0136] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0137] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A packaging material, characterized in that: The packaging material comprises epoxy resin, in which fluorinated polymer filler and nano silicon particles are added.
2. The packaging material according to claim 1, characterized in that The epoxy resin comprises an epoxy resin matrix and a curing agent in a mass ratio of 2:1-4:
1.
3. The packaging material according to claim 2, characterized in that The thermal expansion coefficient of the epoxy resin is 6×10- 6 / K.
4. The packaging material according to claim 2, characterized in that The epoxy resin matrix is epoxy resin 2000, solid bisphenol A epoxy resin, bisphenol F epoxy resin, liquid bisphenol A epoxy resin, glycidylamine epoxy silicone resin or polyisocyanurate-oxazolidone resin.
5. The packaging material according to claim 1, characterized in that The added amount of the fluorinated polymer filler is 5%-10% (v / v).
6. The packaging material according to claim 5, characterized in that The fluorinated polymer filler is polytetrafluoroethylene, polyvinylidene fluoride, fluororubber, fluorinated ethylene propylene rubber, perfluoroether rubber or fluorosilicone rubber.
7. The packaging material according to claim 1, characterized in that The added amount of the nano silicon particles is 0.5wt%-2wt%.
8. The packaging material according to claim 1, characterized in that The diameter of the nano silicon particles is 10-50 nanometers.
9. A method for preparing a packaging material, characterized in that: The method comprises the following steps: uniformly mixing epoxy resin and curing agent, and then sequentially adding fluorinated polymer filler and nano silicon particles therein to obtain the packaging material.
10. A method for reducing microcracks in the production process of solar cell modules, characterized in that: The following steps are involved: The encapsulation material according to any one of claims 1 to 8 is coated on the surface of a solar cell chip, and the encapsulation material is cured at 80-120° C. for 2-4 hours to complete the encapsulation; the encapsulated solar cell chip is assembled with a back plate and a glass cover to obtain the solar cell module.